Kesenjangan Hukum dan Realitas Sosial Terhadap Pekerja Migran Indonesia di Kamboja: Perspektif Yuridis dan Sosiologis - Dian Ratu Ayu Uswatun Khasanah; Ronald Jolly Pongantung; Cynthia Maria Siwi (Integralistik, 2026)
The increasing number of Indonesian illegal migrant workers, particularly from Central Java, reflects the socio-economic disparities in Southeast Asia, especially in relation to unequal opportunities for employment and wages between countries. The driving factors behind this illegal migration include high unemployment rates, poverty in rural areas, and strong social networks, which often encourage prospective workers to choose non-procedural pathways despite the high risks involved. This illegal migration involves informal recruitment by brokers and document falsification, which makes workers vulnerable to exploitation, violence, and human trafficking. Although Indonesia has a relatively comprehensive legal framework through Law Number 18 of 2017 on the Protection of Indonesian Migrant Workers, the implementation of legal protection in practice remains far from satisfactory. Weak law enforcement, limited inter-agency coordination, and a lack of trust in official procedures have led many workers to choose illegal routes. This study identifies the gap between written laws and the social practices of illegal migration through a normative legal and socio-legal approach. The findings show that existing legal policies are not effectively followed in practice, leaving illegal migrant workers still vulnerable. To improve this situation, a more holistic approach is needed, including simplifying legal migration procedures, enforcing stricter laws against illegal recruitment, and strengthening legal education for prospective migrant workers. These findings are expected to contribute to the development of more effective migrant worker protection policies, bridging the gap between existing laws and the reality on the ground.